PENGARUH PENGETAHUAN PAJAK DAN SANKSI PAJAK TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DENGAN KUALITAS PELAYANAN SEBAGAI PEMODERASI - Putri, Destiana Nila; Hunein, Hamida (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This study aims to analyze the effect of tax knowledge and tax sanctions on the level of taxpayer compliance with service quality as a moderator. The dependent variable in this study is the level of taxpayer compliance, the moderating variable in this study is service quality, and the independent variable consists of tax knowledge and tax sanctions. The type of research used is quantitative method. This research was conducted at the Pratama Tax Service Office (KPP) Jakarta Cengkareng in the West Jakarta Region. The sampling method is quota. Questionnaires distributed as many as 100 questionnaires that can be used as data. Data processing using SPSS Version 25 program. The data analysis method used is descriptive statistics, validity tests, reliability tests and classical assumption tests and uses multiple linear regression tests, namely the coefficient of determination test, t test and f test. The results of this study indicate that tax knowledge has a significant effect on the level of taxpayer compliance. Tax sanctions have a significant effect on the level of taxpayer compliance. Moderation of service quality has no effect and weakens the effect of tax knowledge on the level of taxpayer compliance. Moderation of service quality has an effect and strengthens the effect of tax sanctions on the level of taxpayer compliance.